Effect of heteroatom substitution on transport in alkanedithiol-based molecular tunnel junctions: evidence for universal behavior - Xie, Zuoti; Bâldea, Ioan (ACS nano, 2017)
The transport properties of molecular junctions based on alkanedithiols with three different methylene chain lengths were compared with junctions based on similar chains wherein every third −CH2- was replaced with O or S, that is, following the general formula HS(CH2CH2X)nCH2CH2SH, where X = CH2, O, or S and n = 1, 2, or 3. Conducting probe atomic force microscopy revealed that the low bias resistance of the chains increased upon substitution in the order CH2 < O < S. This change in resistance is ascribed to the observed identical trend in contact resistance, Rc, whereas the exponential prefactor β (length sensitivity) was essentially the same for all chains. Using an established, analytical single-level model, we computed the effective energy offset εh (i.e., Fermi level relative to the effective HOMO level) and the electronic coupling strength Γ from the current-voltage (I-V) data. The εh values were only weakly affected by heteroatom substitution, whereas the interface coupling strength Γ varied by over an order of magnitude. Consequently, we ascribe the strong variation in Rc to the systematic change in Γ. Quantum chemical calculations reveal that the HOMO density shifts from the terminal SH groups for the alkanedithiols to the heteroatoms in the substituted chains, which provides a plausible explanation for the marked decrease in Γ for the dithiols with electron-rich heteroatoms. The results indicate that the electronic coupling and thus the resistance of alkanedithiols can be tuned by substitution of even a single atom in the middle of the molecule. Importantly, when appropriately normalized, the experimental I-V curves were accurately simulated over the full bias range (±1.5 V) using the single-level model with no adjustable parameters. The data could be collapsed to a single universal curve predicted by the model, providing clear evidence that the essential physics is captured by this analytical approach and supporting its utility for molecular electronics.